Continuous Functions with Complicated Local Structure Defined in Terms of Alternating Cantor Series Representation of Numbers - Serbenyuk, S.O. (Журнал математической физики, анализа, геометрии, 2017)
The paper is devoted to one infinite parametric class of continuous functions with complicated local structure such that these functions are defined in terms of alternating Cantor series representation of numbers. The main attention is given to differential, integral and other properties of these functions. Conditions of monotony and nonmonotony are found. The functional equations system such that the function from the given class of functions is a solution of the system is indicated.